A rapid noninvasive method to visualize ruptured aneurysms in the emergency room: three-dimensional power Doppler imaging - Perren, Fabienne; Horn, Peter; Kern, Rolf; Bültmann, Eva; Hennerici, Michael G.; Meairs, Stephen (Journal of neurosurgery, 2004)
OBJECT: Three-dimensional (3D) power Doppler ultrasonography imaging provides a rapid, noninvasive visualization of ruptured intracranial aneurysms, including their relationship to other vascular structures. - METHODS: The authors used transcranial 3D power Doppler imaging in the emergency room to examine patients with acute subarachnoid hemorrhage. In all patients, the ruptured aneurysm was rapidly located with 3D power Doppler imaging. Conventional x-ray angiography confirmed both the ultrasonography-based diagnosis and the location of aneurysmal bleeding. - CONCLUSIONS: These preliminary results indicate that 3D power Doppler imaging is a rapid, noninvasive screening method for the visualization of ruptured aneurysms.